2006
DOI: 10.1262/jrd.18019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pueraria mirifica on the Sexual Skin Coloration of Aged Menopausal Cynomolgus Monkeys

Abstract: Abstract. To investigate the estrogenic effect of Pueraria mirifica (PM), a Thai herbal plant that contains many phytoestrogens, sexual skin coloration was studied in cynomolgus monkeys. Aged menopausal monkeys were divided into three groups. Each group (n=3) was fed 10, 100, or 1,000 mg of PM daily. The treatment schedule was divided into three periods, a 30-day pre-treatment period, 90-day treatment period, and 60-day post-treatment period. The results show that the sexual skin exhibited reddish coloration w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…The plant is a rich source of phytoestrogens including mirestrol (13), deoxymirestrol (14) and isoflavonoids (15,16). The plant's powdered tuber has been shown to improve the lipid profiles and biochemical markers of bone turnover rates (17) and the recovery of vaginal health (18) in clinical trials with menopausal Thai females and also to provide other health benefits as demonstrated in animal tests such as prevention of osteoporosis (19,20), breast cancer (21) and estrogen deficiency replacement (22,23). However, there is only one report about this plant that demonstrated the action of the plant phytoestrogens at the ERα and ERβ level (21).…”
Section: Introductionmentioning
confidence: 99%
“…The plant is a rich source of phytoestrogens including mirestrol (13), deoxymirestrol (14) and isoflavonoids (15,16). The plant's powdered tuber has been shown to improve the lipid profiles and biochemical markers of bone turnover rates (17) and the recovery of vaginal health (18) in clinical trials with menopausal Thai females and also to provide other health benefits as demonstrated in animal tests such as prevention of osteoporosis (19,20), breast cancer (21) and estrogen deficiency replacement (22,23). However, there is only one report about this plant that demonstrated the action of the plant phytoestrogens at the ERα and ERβ level (21).…”
Section: Introductionmentioning
confidence: 99%
“…Consumption of the tuberous powder generates a strong estrogenic activity as revealed by the induction of vaginal cornification in ovariectomized rats (5,6) and by the MCF-7 cell proliferation assay (7). Treatment of gonadectomized rats with plant tuber powder resulted in a reduction of LH and FSH levels (8), with dose-dependent estrogenic responses in female mice (9), female monkeys (10), and menopausal monkeys (11)(12)(13). The plant tuber powder also elicits dose-dependent physiological responses in male mice with a reduction in the weight of the epididymis and the seminal vesicles and reduced sperm motility and viability (14), promoting protection against osteoporosis in orchidectomized male (15) and female rats (16).…”
Section: Introductionmentioning
confidence: 99%
“…In aged menopausal monkeys, consumption of crude powder from the plant decreases the concentrations of FSH and LH [12] and parathyroid hormone (PTH) [13] and induces reappearance of sexual skin [14]. Consumption of a high amount of P. mirifica caused disruption of male sex organs, including the epididymis and seminal vesicle, and affects sperm motility and viability [15] but leads to protection against osteoporosis in orchidectomized rats [16].…”
mentioning
confidence: 99%